PENINGKATAN DAYA SAING USAHA TAHU GEDONGARUM MELALUI PENDAMPINGAN BISNIS TERPADU - Azhari; Suhartono, Edy; Ramadhani, Rizka Syahira; Amanda, Serli Ayu (Universitas Kadiri, 2025)
Mentoring for Tofu SMEs in Gedongarum Village, Bojonegoro, was conducted to address obstacles faced by business owners, particularly those related to a lack of marketing knowledge, limited technological promotion, and low product competitiveness in the market. The objective of this activity was to help business owners develop marketing strategies, improve their digital technology skills, and expand market access for better business growth. The mentoring was implemented in three stages: field surveys, technical assistance, and evaluation. The survey was conducted through interviews with business owners, technical assistance provided guidance and practical training, while evaluation was conducted to assess the program's effectiveness. The results of the activity showed an increase in business owners' skills in digital marketing, which resulted in increased tofu sales.